Educação na cultura digital : percepções sobre as práticas pedagógicas de professores do ensino fundamental - Correa, Thatiany Soares (2023)
Considering the advent of digital culture in our society, new forms of interaction between people emerge within the scope of a phenomenon that, in turn, engenders transformations in the way we communicate, relate and learn. In the context of education, digital culture points to new possibilities for teachers' pedagogical practice, which suggests a reconfiguration of teaching activities with the use of different digital resources and technologies. In view of this, we established the research's guiding question: How are the pedagogical practices of elementary school teachers being constituted from the use of digital technologies in school activities? To carry out this research, we obtained approval from CEP- Humanidades under opinion nº 5.165.003. This is an exploratory and descriptive research with a qualitative approach, whose objective was to understand the pedagogical practices of Elementary School teachers in the current digital culture. And, as specific objectives, we seek: To apprehend the understandings and perceptions of teachers about digital culture; Identify how social practices of digital culture are being developed in teachers' pedagogical practices; Understand teachers' perceptions about the configurations of their current pedagogical practices. To carry out the investigation, the research was carried out in two stages: in the first, based on the systematic review, we carried out a survey of productions on pedagogical practices, digital technologies and education; in the second, we used document analysis, a questionnaire and semi-structured interviews to generate data. The research participants were teachers working in elementary education in different areas of knowledge at two public schools in Cuiabá. For data analysis, we based ourselves on content analysis and constituted four units of meaning. At the limit of the analyzes carried out, we inferred that teachers recognize the resonance of digital technologies in their activities from a perspective of interaction, communication, sharing and action in society. The analyzes also reveal that the transposition of digital culture practices into their teaching activities allows the organization of a new pedagogical practice, enriched by the diversity of artifacts and existing connections, providing information and content with a plurality of accesses. In other words, it reveals the movement of reconfiguration of teaching practices aligned with social practices inherent to digital culture.